MENGGALI PELUANG DAN MENYIKAPI TANTANGAN BERKATEKESE DIGITAL BAGI GENERASI ALPHA - Latief, Theresia Vita Prodeita (Lembaga Penelitian STKIP Widya Yuwana, 2025)
Generation Alpha was born in a highly connected digital era, resulting in a different educational environment than previous generations. This study examines the opportunities and challenges associated with digital catechesis in shaping the faith, hope, and love of Generation Alpha. Through a qualitative research methodology with a literature review, the author identified a gap in the results of previous studies related to Generation Alpha, namely the absence of research on the opportunities for digital catechesis for the faith education of Generation Alpha within the Catholic Church. The author analyzes the characteristics of Generation Alpha and the various opportunities and challenges that arise in digital catechesis to nurture their faith. The research findings indicate that Generation Alpha can respond positively to digital catechesis, seeing it as an opportunity to explore the teachings of faith in a complex digital landscape. However, challenges remain, such as concerns about the appropriateness of content and user safety. The role and efforts of parents, catechists, and educators in schools in instilling and educating the faith of Generation Alpha children are highly influenced by the advancement of today's digital technology. Digital catechesis is a method of faith education that utilizes digital technology to convey Christian beliefs and moral teachings, becoming increasingly important in its development and implementation to Generation Alpha. Therefore, the involvement of parents, catechists, and educators in schools is crucial to guide and support the development of the faith of Generation Alpha through digital catechesis.